Concession behaviour in automated negotiation - Lopes, Fernando (2011)
Traditional negotiation, conducted face-to-face and via mail or telephone, is often difficult to manage, prone to misunderstanding, and time consuming. Automated negotiation promises a higher level of process efficiency, and more importantly, a faster emergence and a higher quality of agreements. The potential monetary impact has led to an increasing demand for systems composed of software agents representing individuals or organizations and capable of reaching efficient agreements. At present, work on automated negotiation has generated many useful ideas and concepts leading to important theories and systems. Yet, the design of software agents with negotiation competence largely lacks systematic, traceable, and reproducible approaches, and thus remains more an art than a science. Against this background, this paper presents a model for software agents that handles two-party and multi-issue negotiation. The model incorporates various concession strategies and negotiation tactics. Concession strategies are computationally tractable functions that define the tactics to be used both at the outset and throughout negotiation. Tactics, in turn, are functions that specify the short-term moves to be made at each point of negotiation.